KAJIAN YURIDIS TENTANG PENGALIHAN HAK CIPTA BUKU MELALUI PERSPEKTIF HUKUM WARIS PERDATA DI INDONESIA - Andiza, Dina; Marbun, Rika Jamin (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Copyright as an intangible movable object has Economic Right and Moral Right which can be transferred through inheritance. However, Law Number 28 of 2014 concerning Copyright does not explain and regulate in detail the procedure for transferring Copyright by inheritance. As for the transfer of Copyrights including Copyrights to Book Works, it must be submitted with an application for registration at the Directorate General of Intellectual Property (Dirjen IP) and announced in the Official Gazette at the Director General of Intellectual Property Rights. As for the transfer of Copyrights including Copyrights to Book Works, it must be submitted with an application for registration at the Directorate General of Intellectual Property (Dirjen IP) and announced in the Official Gazette at the Director General of Intellectual Property Rights. The problem is how to regulate the law regarding Copyright for Book works and how is the juridical study regarding the transfer of Copyright for Book works viewed from the perspective of Civil Inheritance Law in Indonesia. While the aim of the research is to find out the legal arrangements regarding Copyrights to Book works and to find out juridical studies regarding the transfer of Copyrights to Book works from the perspective of Civil Inheritance Law in Indonesia. The writing of this article uses the type of Normative Legal Research with the method of collecting library research data and the type of data from secondary data, which comes from official documents, books, scientific journals, the internet and laws and regulations. Transfer of Copyright through inheritance can be carried out after the death of the Author or Copyright Holder and the inheritance is automatically given to the Heirs. It is hoped that the government will provide counseling to the public regarding Copyright, especially Book works and Authors of Books can transfer their creations by submitting an Application for Registration at the Directorate General of Intellectual Property (Dirjen KI) in Jakarta or through the Regional Offices of the Ministry of Law and Human Rights in the regions. Keywords : Juridical Studies, Transfer of Book Copyrights and Perspectives on Civil Inheritance Law